El texto de Isócrates del Salmanticensis 279 - Martínez Manzano, Teresa (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2006)
The aim of this paper is to study the history of this manuscript and to analyze its place in the transmission of the text of seven discourses by Isocrates.